Ambient fine particulate matter air pollution and the risk of preterm birth: A multicenter birth cohort study in China. (15th October 2021) - Chu, Chen; Zhu, Yixiang; Liu, Cong; Chen, Renjie; Yan, Yingliu; Ren, Yunyun; Li, Xiaotian; Wang, Jimei; Ge, Wenzhen; Kan, Haidong; Gui, Yonghao
Abstract: Preterm birth (PTB), defined as live birth before the 37th week of gestation, is believed to have profound impacts on the infant's health in later life. Air pollution has been suggested to be a potential risk factor of PTB, but the evidence was inconsistent. In this multicenter birth cohort study, we aimed to examine the association between fine particulate matter (PM2.5 ) exposure during pregnancy and PTB in China. A total of 5976 live births were identified between Jan. 2009 and Feb. 2011 from 8 provinces in China. Residential exposures to PM2.5 were assigned based on satellite remote sensing estimates. Cox proportional hazards regressions were employed to explore the correlation for each trimester as well as the entire pregnancy. A total of 443 (7.4%) preterm births were observed. The average PM2.5 during pregnancy was 57.2 ± 8.8 μg/m 3 . We found exposure to PM2.5 during the whole pregnancy (hazard ratio, HR = 1.262; 95% CI: 1.087–1.465) and in the first trimester (HR = 1.114; 95% CI: 1.007–1.232) was associated with higher risk of PTB. The associations of PM2.5 were stronger for subjects with older maternal or paternal age, lower maternal pre-pregnancy BMI, and lower family income. This study adds supports to the cumulating evidence linking PM2.5 exposure and elevated PTB risk. Measures of air pollution reduction are needed during pregnancy, especially at early stage of pregnancy to prevent adverse birth outcomes. Graphical abstract: Image 1 Highlights: Prenatal exposure to PM2.5 was associated with preterm birth risk. The first trimester of pregnancy may be a critical exposure time window. Parental age, pre-pregnancy BMI, and family income may be potential modifiers.